Examine the Relationship between Hospital Information Systems and Improving Accountability of Nurses - Maroofi, Fakhraddin (International Journal of Asian Social Science, 2016)
The aim of this research is correlational and 216 questionnaires were designed and collected by the researcher. The measurement of the reliability and validity of the questionnaire and a pilot study was (30 people) conducted reliability tests using Cronbach’s alpha for hospital information system (.606) and for improving accountability (.786). The results showed a positive and significant relationship between hospital information system and improve accountability exists (R = .310, significant = .000), between users’ satisfaction and quality improvement system. There is a positive relationship between accuracy, quality of information content; information and access to information have improved the response and positively related and significant. The lack of relationship between users’ satisfaction and quality improvement system meets the expressed need for administrators to upgrade the system software and hardware to better satisfy its users to increase the efficient use of hospital accountability level hospital information system.